Outside the bed of time: On some Brechtian motifs in Walter Benjamin - Chiaravalli, Iacopo (Scenari, 2022)
The present article aims to disentangle the difficult relation between Benjamin and Brecht. The starting point of the argument is Adorno’s famous objections against Benjamin’s The Work of Art in the Age of Its Technological Reproducibility. The first step is showing that what Adorno finds challenging in the Art-Work Essay has not a Brechtian origin. Then, the second step deals with the way Benjamin reads Brecht’s epic theatre as a source of the so called profane illumination. This is possible thanks to a concept of dialectics completely different from Brecht’s reflection on dialectics. That makes possible to argue that Adorno has an image of Brecht mediated through Benjamin’s interpretation of the epic theatre. As a conclusion I try to make the point that Brecht is much closer to Adorno than to Benjamin on those specific questions which Adorno considers problematic in Benjamin’s conception of technology and art.